THE ANALYSIS OF THE EFFECTIVENESS OF RECEIVABLES CONTROL IN CASH FLOW REPORTS DURING PANDEMIC RECOVERY AT KOKOON HOTEL BANYUWANGI - Salsabilla Hervinta Putri; Ahmadintya Anggit Hanggraito; Auda Nuril Zazilah (Jurnal RAK (Riset Akuntansi Keuangan), 2023)
This study aims to analyze the receivables control effectiveness in cash flow reports during pandemic recovery at Kokoon Hotel Banyuwangi. The Banyuwangi Covid-19 pandemic was first confirmed on March 29 2020. Kokoon Hotel was one of the hotels affected by the pandemic, meanwhile in 2022 begin the recovery stages. The recovery from pandemic has increased the expenses, income and room occupancy rates. The occupancy rate influences room sales by cash or credit system. Credit sales affect the cash flow report and require effective control of receivables to anticipate delays in receivable payments. The research approach used is a qualitative descriptive and employ an observation, interviews and documentation as the data collection techniques. Data analysis used is receivables turnover rate and descriptive analysis. The results showed that control of receivables is effective. There is an increase of 7.89% in receivables collection from the first semester to the second semester of 2022.